Epidemiological profile of 277 patients with facial fractures treated at the emergency room at the ENT Department of Hospital do Trabalhador in Curitiba/PR, in 2010 - Ykeda, Renier Barreto Arrais; Ballin, Carlos Roberto; Moraes, Rafael Souza; Ykeda, Ronnie Barreto Arrais; Miksza, Alana Farias (International Archives of Otorhinolaryngology, 2012)
Introduction: Epidemiological studies that focus on facial injuries are of great interest for the knowledge of occurrence and severity of presentation.Aim: To study the epidemiological profile of 277 patients who suffered facial fractures at the Hospital do Trabalhador (HT), with an emphasis on variables such as sex, age, cause, and anatomical sites of fractures, comparing the clinical findings with other studies.Method: Retrospective nonrandomized chart review of 277 patients who were treated at HT by the ENT service during the full year 2010, victims of facial fractures.Results: Of 277 patients, 74.72% were male and 25.27% female (ratio 3:1). According to age, the fractures were distributed as follows: 0–9 years: 4.69%, 10–19 years: 17.32%, 20–29 years: 23.82%, 30–39 years: 20.21%, 40–49 years: 16.24%, 50–59 years: 10.83%, 60–69 years: 3.97%, and 60–79 years: 2.88%. The cause of trauma was most frequently interpersonal violence, 36.45%, followed by falls, 23.09%, and motor vehicle crashes with 17.32%. Regarding location, nasal fracture was the most common, with 44.75%, followed by the mandible, 14.32%, orbit, 12.78%, maxillary, 12.02%, zygomatic, 9.97%, 3.32% and front Le Fort 2.88%.Conclusion: The patients were mostly males, aged 21–30 years, victims of aggression with the most commonly fractured bone being the nose. The adoption of personal and public strategies and measures may prevent facial fractures.
Keywords: epidemiology; maxillofacial injuries; face